7 Hypoglycaemia and Higher Levels of Homocysteine are Asscociated with Watershed and White Matter Injury in Neonatal Encephalopathy Following Hypoxia-Ischemia. (October 2012) - Harteman, J; Groenendaal, F; Benders, M; Huisman, A; Blom, H; Vries, L de
Abstract : Objective: Neonatal encephalopathy (NE) is a serious condition, primarily seen following hypoxia-ischemia. Different patterns of brain injury can be recognised following perinatal hypoxia-ischemia (HI). Whether these patterns of injury can be attributed to different associated risk factors still needs to be established. Aim: To identify the association of antenatal, perinatal and thrombophilic risk factors in infants with NE following HI with pattern of brain injury. Methods: In 110 infants with clinical signs of NE following perinatal HI, thrombophilic factors were prospectively investigated. These included factor V Leiden and prothrombin gene mutation, C677T and A1298C polymorphisms in the MTHFR gene and plasma levels of homocysteine and lipoprotein(a). Antenatal and perinatal variables were studied. Results: White matter/watershed injury was seen in 44 infants (40%), basal ganglia/thalamus injury in 34 (31%) and normal neuro-imaging in 32 infants (29%). Antenatal factors did not differ across the different patterns of injury. The basal ganglia/thalamus pattern was associated with emergency Cesarean section. White matter/watershed pattern was associated with hypoglycaemia (< 2.0 mmol/L) (OR 5.3; 1.6–17.8 (95% CI)), CT or TT 677 polymorphism in the MTHFR gene and plasma homocysteine levels in the upper quartile (OR 2.9; 1.01–8.4 (95% CI)) compared to the no injury group. Conclusion: Across three patterns of injury in infants with NE following perinatal HI, predominant white matter/watershed pattern was associated with hypoglycaemia, the MTHFR 677CT or TT genotype, and higher levels of plasma homocysteine. Basal ganglia/thalamus injury showed an association with signs suggestive for more severe, acute HI.